A study of non-governmental organisations involved in meeting the ne eds of persons with disabilities in Uganda: final report - Ocitti, Jakayo Peter (Kampala: Makerere university, 1993)
DANIDA/UNISE Programme, Ministry of education and Sports
Includes bibliographical references (p.44-45)
Keywords: Handcapped -- Services for